REMEDIASI MISKONSEPSI MENGGUNAKAN STRATEGI PREDICT, DISCUSS, EXPLAIN,OBSERVE, DISUCSS, EXPLAIN (PDEODE) TENTANG MOMENTUM DAN IMPULS PESERTA DIDIK SMA NEGERI 1 SELIMBAU - Yeni Apriyanti; Stepanus Sahala Sitompul; Muhammad Musa Syarif Hidayatullah (Universitas Tanjungpura, 2021)
AbstractThis study aimed to assess the effectiveness of misconception remediation using predict, discuss, explain, observe, discuss, explain (PDEODE) strategies on momentum and impulse of students at SMAN 1 Selimbau. The method used in this research was a pre-experimental design with one group pre-test post-test design. Samples of study were intact group and selected based on physics teacher’s recommendation. The research instrument included 8 questions of diagnostic test. The percentage number of students with misconceptions of each indicator and student was reduced to 69,38% and 71,80%. Based on the results of the McNemar test, overall students experienced significant conceptual changes with a value of X 2 count(67.37)> χ 2 table (3.84) with df = 1 and α = 5%. The effectiveness using PDEODE strategies to remediate the number of student’s misconception through DQM of 68,98% which is included to medium category. This research is suggested to be use as an alternative learning activity to reduce the number of students that have misconception on momentum and impulse.Keywords: Misconception Remediation, Momentum and Impuls, Predict, Discuss, Explain, Observe, Discuss, Explain (PDEODE)